Transforming Roadside Gardens into Responsible Tourist Attractions: A Conceptual Framework - Mamboleo, Abel Ansporthy (Eco-Tourism and Sustainable Development, 2026)
This study investigates the potential of Tanzanian roadside gardens as sustainable tourism assets for urban tourism development. Studies demonstrate that casual roadside gardens enhance urban aesthetics and provide income for casual roadside gardeners. Despite their usefulness, their potential remains largely untapped by urban planners and tourism stakeholders. The research adopted Leiper’s attraction system model and responsible tourism principles to conceptualize the transformation of casual roadside gardens as responsible tourist destinations. Six main themes were identified through systematic literature review and thematic content analysis, which included tourist experience, urban infrastructure, responsibility and ethics, digitalization, cultural authenticity, and regional coverage, as the themes demonstrated their links and ability to create both experiential and sustainable tourism. The results show that roadside gardens function as multipurpose areas that support environmental conservation, protection of cultural heritage, and active participation of local communities. The study presents a flexible framework that enables policymakers and urban planners to transform informal green spaces into official sustainable urban development pathways that will empower communities while protecting ecological environments and preserving cultural heritage. The framework provides a roadmap for transformation of roadside gardens into responsible tourist attractions, benefiting roadside gardens socioeconomically and environmentally.